2020
DOI: 10.1155/2020/4326549
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Gastric Bypass in Obese Diabetic Rats Promotes Autophagy to Improve Lipid Metabolism through mTOR/p70S6K Signaling Pathway

Abstract: Purpose. To investigate the effects of Roux-en-Y gastric bypass (RYGB) surgery on markers of liver mitochondrial dynamics and find new therapeutic basis on obese type 2 diabetes mellitus (T2DM) patients. Materials and Methods. Thirty-two rats were divided into nondiabetic group, diabetic group, sham group, and RYGB group. The Dual-energy X-ray absorptiometry (DEXA) was used to detect short-term curriculum vitae for rat body component and fat and lean mass. Hepatic lipid content and triglyceride levels were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Accordingly, high-fat fed rats submitted to sleeve gastrectomy showed significant TG reduction, and lower markers of ER stress and UPR activation, accompanied by increased β-oxidation, AMPK and autophagic activation (Ezquerro et al, 2016(Ezquerro et al, , 2020. Similar changes were found using roux-en-Y gastric bypass interventions (He et al, 2015;Ma et al, 2020). ER stress and UPR activation are common findings in the steatotic liver of rodents and humans, and many targets have been suggested as possible points of intervention for NAFLD treatment (Lebeaupin et al, 2018).…”
Section: Diet-induced Steatosis Models Diets Enriched In Fatmentioning
confidence: 80%
See 1 more Smart Citation
“…Accordingly, high-fat fed rats submitted to sleeve gastrectomy showed significant TG reduction, and lower markers of ER stress and UPR activation, accompanied by increased β-oxidation, AMPK and autophagic activation (Ezquerro et al, 2016(Ezquerro et al, , 2020. Similar changes were found using roux-en-Y gastric bypass interventions (He et al, 2015;Ma et al, 2020). ER stress and UPR activation are common findings in the steatotic liver of rodents and humans, and many targets have been suggested as possible points of intervention for NAFLD treatment (Lebeaupin et al, 2018).…”
Section: Diet-induced Steatosis Models Diets Enriched In Fatmentioning
confidence: 80%
“…In fact, liver-specific AMPK activation was shown to counteract steatosis development during obesity by different mechanisms, including autophagy activation . Bariatric surgery in rodents, for instance, improves steatosis while increasing AMPK and decreasing mTORC1 activation (Ezquerro et al, 2016;Ma et al, 2020). Moreover, increased cytosolic acetyl-CoA derived from peroxisomal β-oxidation present in the liver of HFD fed animals was shown to promote mTOR localization at the lysosome surface, increasing ULK1 phosphorylation by mTORC1 and inhibiting autophagy (He et al, 2020).…”
Section: Mechanisms Of Autophagy Impairment In Nafldmentioning
confidence: 99%
“…However, few studies have evaluated the possible interaction between autophagy and weight loss in obese models. Previous research has shown that the downregulation of hepatic autophagy in high-fat diet-induced obesity promotes ER stress and IR [ 51 , 52 ], whereas RYGB is reported to improve hepatic lipid metabolism through an increase in the LC3-II/LC3-I ratio and the down-regulation of mTOR [ 53 ]. In the case of 3T3-L1 preadipocytes, the recent report published by Zhang et al [ 54 ] points to autophagy as the molecular effector that restores lipid accumulation in adipocytes through activation of autophagy and chaperone-mediated autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that high levels of FFA inhibit GLP-1 [30]. Inhibiting FFA levels can increase GLP-1 secretion, thereby improving T2DM [7,31]. Studies have shown that BHB signi cantly improved tissue damage, metabolic disorders and protein metabolism [32].…”
Section: Discussionmentioning
confidence: 99%